Self‐assembling chitosan hydrogel: A drug‐delivery device enabling the sustained release of proteins. Issue 1 (15th August 2017) - Kiene, Klara; Porta, Fabiola; Topacogullari, Buket; Detampel, Pascal; Huwyler, Jörg
ABSTRACT: The development of a self‐assembling hydrogel, prepared from maleimide‐modified and thiolated chitosan (CS), is described. Under mild reaction conditions, the natural CS polymer was coupled with either maleimide or sulfhydryl moieties in a one‐step synthesis. Subsequently, these CS polymers spontaneously formed a covalently crosslinked CS hydrogel when mixed. The three‐dimensional network structure was visualized with scanning electron microscopy. The swelling and degradation behavior was evaluated, and viscosity measurements were conducted. The gel was loaded with the model protein albumin, and prolonged release was achieved. These properties were preserved after lyophilization and rehydration. This makes the hydrogel a promising scaffold for biological wound dressings for the treatment of chronic wounds. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45638. Abstract :